1989
DOI: 10.1149/1.2096498
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Copper from Copper (II) Hexafluoroacetylacetonate

Abstract: Thermally activated decomposition of the vapor phase of copper (II) hexafluoroacetylacetonate was studied. It was found that the temperature at which the decomposition is carried out influences dramatically the chemical composition of deposits; the higher the temperature, the more carbon is incorporated. Pure copper deposits having resistivities of 3–7 μΩ cm were obtained at substrate temperatures of 340°–390°C. It is believed that in this temperature range, breaking of the metal‐ligand bond of the copper comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(56 citation statements)
references
References 9 publications
2
54
0
Order By: Relevance
“…These differences are not surprising since the observed apparent activation energies are the result of several processes [24][25][26] and, therefore, can be affected by the different conditions adopted for ex-situ TG and in-situ FTIR measurements. In addition, in-situ FTIR data obtained during real MOCVD processes depend on the precursor partial pressure and, in turn, on the balance between the precursor vaporization rate and the carrier gas flow rate.…”
Section: Evaporation/sublimation Processmentioning
confidence: 97%
“…These differences are not surprising since the observed apparent activation energies are the result of several processes [24][25][26] and, therefore, can be affected by the different conditions adopted for ex-situ TG and in-situ FTIR measurements. In addition, in-situ FTIR data obtained during real MOCVD processes depend on the precursor partial pressure and, in turn, on the balance between the precursor vaporization rate and the carrier gas flow rate.…”
Section: Evaporation/sublimation Processmentioning
confidence: 97%
“…These results imply that any carbon and oxygen on the surface can thus be ascribed to atmospheric contamination when the samples were exposed to air, and not to the ligand hfac of the precursor molecule decomposing on the surface of the substrate to leave impurities in the deposited film. [14,15] The ratio of the peak intensities of Cu(111) and Cu(200) is a key feature in the EM resistance of copper films. [16,17] It was investigated by XRD in this work.…”
Section: Evolution Of Surface Morphologymentioning
confidence: 99%
“…[16,17] It was investigated by XRD in this work. Figure 5 shows In our previous work, [18] and that of Temple and Reisman, [15] in which depositions were carried out on either bare silicon wafers or oxidized ones, it needed higher temperatures on such substrates to obtain high-quality copper films. The results of these studies showed that pure copper films were obtained at temperatures of 340-390°C, compared to the 290-350°C in this current work.…”
Section: Evolution Of Surface Morphologymentioning
confidence: 99%
“…The most popular until now, in spite of being solid at room temperature, is bis-hexafluoroacetylacetonato copper, Cu(hfa)2, as shown in Fig. 1 [14,15]. This is due to its stability, low toxicity and relatively high volatility (p~ 10 -2 torr or 1.3 Pa at 300 K) improved by substituting fluorine atoms for hydrogen atoms in the acetylacetonato ligand.…”
Section: 3 Copper Precursormentioning
confidence: 99%